Prevalence of preeclampsia and associated factors among pregnant women delivering in Vietnam: a cross-sectional study - Nguyen, Yen; Ho, Tuan; Lam, Hoai-Thanh; Tran, Anh; Pham, Huyen; Nguyen, Sang (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Preeclampsia is a leading cause of maternal and fetal mortality and morbidity globally. This study aims to determine the prevalence of preeclampsia and identify associated factors among pregnant women presenting for delivery in Ho Chi Minh City, Vietnam. Methods: A cross-sectional descriptive study was conducted on 386 pregnant women with a gestational age greater than 20 weeks presenting for delivery in Ho Chi Minh City, Vietnam. Data were collected via direct interviews and medical record reviews. Variables were analyzed using Chi-square and Fisher’s exact tests. Results: The prevalence of preeclampsia in the study group was 2.59% (10/386). Factors showing a statistically significant association (p < 0.05) with preeclampsia included: place of residence (non-urban areas had a higher risk), religion, mode of previous delivery, history of preterm birth, and history of miscarriage. No statistically significant association was found between preeclampsia and age group, occupation, education level, body mass index (BMI), smoking/alcohol habits, or family history. Conclusions: The prevalence of preeclampsia among pregnant women delivering in Ho Chi Minh City is 2.59%. Identifying associated factors, such as adverse obstetric history and geographical factors, is essential to improve screening and pregnancy management.